Research Note: Nowcasting Tourist Arrivals in Barbados – Just Google it!. (December 2015) - Jackman, Mahalia; Naitram, Simon
This paper uses support vector regressions (SVRs) and Google search data to test whether observing Internet habits can provide insights into trends in tourist arrivals in Barbados. The empirical evidence suggests that Google Trends data may be used to pick up changing patterns and trends in tourist arrivals from the UK and Canada. In the case of the USA, the authors find no evidence to suggest that Google data add any significant information to what can be 'learned' from an autoregressive SVR.